ANALYZING FACTORS INFLUENCING SECOND LANGUAGE ACQUISITION IN AL-GHIFARI ISLAMIC BOARDING SCHOOL YOGYAKARTA - Dimas Bagus Wiranatakusuma; Anwar Allah Pitchay (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2020)
Background - The internationalization of education is of increasing importance to many institutions in the world, including at non-formal educational institution. The study aims at analyzing factors influencing second language acquisition (SLA) at Islamic Boarding School Al-Ghifari Yogyakarta, Indonesia. Literature Review – Some literatures argue that there are non-conclusive studies on suggesting factors affecting the SLA in educational institutions. However, after reviewing some studies, internal factor – motivation, and external factors – social environment, teacher, and material, are of some frequently mentioned as the important variables. Data and Methodology - The study employs quantitative technique by applying the multiple regression with the data taken through questionnaire of 18 Islamic boarding school’s students. Findings – The findings show that variable teacher and social environment have positive and significant affect to SLA, meanwhile motivation and material have negative, but insignificant. The reasons are due to students have inner motivation and limited facilities to access English material, but they are exposed with competence teacher and surrounded with conducive English environment. Conclusion and Recommendation – It is relevant and timely to support them with Program Pengabdian Masyarakat with the focus on English learning program. This program can develop and improve the social environment and equip them with more experience and knowledge on how to master English, supported by foreign teacher and innovative teaching method. However, the study needs to consider the SLA with taking attention to specific English skill, such as writing, listening, reading, and speaking. The Significance – The study significantly contributes to the important factors on SLA among students at non-formal educational institution which is rarely discussed.